Culturomics of the plant prokaryotic microbiome and the dawn of plant-based culture media – A review - Mohamed S. Sarhan; Mervat A. Hamza; Hanan H. Youssef; Sascha Patz; Matthias Becker; Hend ElSawey; Rahma Nemr; Hassan-Sibroe A. Daanaa; Elhussein F. Mourad; Ahmed T. Morsi; Mohamed R. Abdelfadeel; Mohamed T. Abbas; et al. (Journal of Advanced Research, 2019)
Improving cultivability of a wider range of bacterial and archaeal community members, living natively in natural environments and within plants, is a prerequisite to better understanding plant-microbiota interactions and their functions in such very complex systems. Sequencing, assembling, and annotation of pure microbial strain genomes provide higher quality data compared to environmental metagenome analyses, and can substantially improve gene and protein database information. Despite the comprehensive knowledge which already was gained using metagenomic and metatranscriptomic methods, there still exists a big gap in understanding in vivo microbial gene functioning in planta, since many differentially expressed genes or gene families are not yet annotated. Here, the progress in culturing procedures for plant microbiota depending on plant-based culture media, and their proficiency in obtaining single prokaryotic isolates of novel and rapidly increasing candidate phyla are reviewed. As well, the great success of culturomics of the human microbiota is considered with the main objective of encouraging microbiologists to continue minimizing the gap between the microbial richness in nature and the number of species in culture, for the benefit of both basic and applied microbiology. The clear message to fellow plant microbiologists is to apply plant-tailored culturomic techniques that might open up novel procedures to obtain not-yet-cultured organisms and extend the known plant microbiota repertoire to unprecedented levels. Keywords: Plant microbiome, Metagenomics, Plant-based culture media, Culturomics, Unculturable bacteria, Candidate Phyla Radiation (CPR)